Profiling of human and microbial cell-free DNA reflects early host–pathogen interactions in sepsis - Hoeter, Katharina; Neuberger, Elmo W. I.; Marriott, Linda; De Falco, Alfonso; Wiemann, Stephanie; Schäfer, Michael K. E.; Simon, Perikles; Kersaudy-Kerhoas, Maïwenn; Bodenstein, Marc (Frontiers in Immunology, 2026)
ObjectivesIn sepsis, circulating cell-free DNA (cfDNA) originates from host cells (damage-associated molecular patterns, DAMPs) and pathogens (pathogen-associated molecular patterns, PAMPs), contributing to immune activation and offering potential as both a biomarker and a therapeutic target. While DAMPs are thought to predominate in early sepsis, this study aimed to quantify their relative abundance and assess their correlation with inflammatory markers compared to PAMPs.MethodsIn this prospective observational study, blood samples of 18 ICU patients were collected within 24 hours of sepsis diagnosis. Plasma cfDNA was analyzed via qPCR (targeting human LINE-1) and iSEP-SEQ nanopore sequencing. Human and microbial cfDNA were quantified, and method correlation was assessed using Kendall’s tau-b correlation. Associations with inflammatory biomarkers were tested using Spearman correlation analysis and group comparisons between human and non-human reads were analyzed with Pearson correlation analysis. The study received ethical approval from the Landesärztekammer Rheinland-Pfalz (Approval Number: 2020-15535).ResultscfDNA was predominantly of human origin, comprising 99.86% of classified reads, with microbial cfDNA accounting for only 0.077% (p < 0.001). qPCR-based cfDNA concentrations strongly correlated with human read counts from sequencing (τ = 0.712; p < 0.001). Human cfDNA levels were significantly associated with LDH, WBC, and CRP. Microbial cfDNA, although low in abundance, correlated with WBC, CRP, and D-dimer.ConclusionsIn early sepsis, human cfDNA is markedly more abundant than microbial cfDNA. However, both exhibit strong correlations with inflammatory and tissue injury markers. These findings support a model of PAMP-triggered and DAMP-driven inflammation and identify human cfDNA as a promising biomarker and potential therapeutic target.Clinical Trial Registrationhttps://drks.de/search/de/trial/DRKS00025222/details, identifier DRKS-ID: 00025222.